2021
DOI: 10.1016/j.chom.2020.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The Early Evolution of Oral Poliovirus Vaccine Is Shaped by Strong Positive Selection and Tight Transmission Bottlenecks

Abstract: Summary The emergence of circulating vaccine-derived polioviruses through evolution of the oral polio vaccine (OPV) poses a significant obstacle to polio eradication. Understanding the early genetic changes that occur as OPV evolves and transmits is important for preventing future outbreaks. Here, we use deep sequencing to define the evolutionary trajectories of type 2 OPV in a vaccine trial. By sequencing 497 longitudinal stool samples from 271 OPV2 recipients and household contacts, we were able t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…Specimen viral load is important when measuring intrahost diversity. We and others have shown that samples with low viral loads are prone to false positive iSNV and lower sensitivity [22,23,30]. A strength of our study is that we experimentally validated the accuracy of our variant calling by sequencing defined populations.…”
Section: Discussionmentioning
confidence: 72%
“…Specimen viral load is important when measuring intrahost diversity. We and others have shown that samples with low viral loads are prone to false positive iSNV and lower sensitivity [22,23,30]. A strength of our study is that we experimentally validated the accuracy of our variant calling by sequencing defined populations.…”
Section: Discussionmentioning
confidence: 72%
“…Specimen viral load is important when measuring intrahost diversity. We and others have shown that samples with low viral loads are prone to false positive iSNV and lower sensitivity 22 , 23 , 29 . A strength of our study is that we experimentally validated the accuracy of our variant calling by sequencing defined populations.…”
Section: Discussionmentioning
confidence: 83%
“…After the initial replication period of the OPV strains, the subsequent mutations would accumulate at a nearly uniform rate of 1 to 2% nucleotide changes per year [ 32 , 50 , 51 ]. Due to a strong positive selection in vaccinees immunized with type 2 OPV, the so-called gatekeeper mutations from the attenuated Sabin 2 strain, including three mutations at A481G, U2909C (VP1-I143T), and U398C, are rapidly selected and fixed in the first several weeks post-vaccination [ 35 , 52 , 53 ]. Those gatekeeper mutations may contribute to the virus replication fitness in the human intestine and higher initial evolution rates of iVDPV and cVDPV immediately after the OPV administration.…”
Section: Genetic Analysis and Molecular Characterization Of Ivdpv2 Isolatesmentioning
confidence: 99%
“…Historically, poliovirus quasi-species were analyzed by the conventional plaque cloning and Sanger sequencing of virus isolates. Recently, next-generation sequencing (NGS) technologies were applied to study viral quasi-species and the molecular evolution of various RNA viruses, including those of the OPV strains and cVDPVs, but not for those from iVDPV cases [ 25 , 52 , 53 ]. In the future, more comprehensive and quantitative analyses on the genetic diversity of the quasi-species of iVDPV variants in infected individuals, compared to those in cVDPV and OPV strains, using NGS will be required.…”
Section: Genetic Analysis and Molecular Characterization Of Ivdpv2 Isolatesmentioning
confidence: 99%
See 1 more Smart Citation